Recommended reporting format for flow cytometry diagnosis of acute leukemia - L Del Vecchio; B Brando; F Lanza; C Ortolani; G Pizzolo; G Semenzato; G Basso; Italian Society for Cytometry (Haematologica, 2004)
Although flow cytometry is increasingly used as a tool to diagnose hematologic malignancies, the reporting format of acute leukemia immunodiagnosis is still imprecise and sometimes vague, often reflecting old guidelines. Thus, the purpose of the present work was to make the reporting format for the immunological diagnosis of acute leukaemia easy and clear to understand. This work represents part of a more articulated series of technical guidelines that the Italian Society for Cytometry (GIC) is currently processing. Thirteen separate recommendations, covering all aspects of an acute leukemia cytometry report, are listed. According to our suggestions, the report must contain clear statements about: 1. demographic identification of patient; 2. identification of the hospital or division sending the sample; 3. type of specimen (bone marrow aspirate, peripheral blood, other biological fluids); 4. timing of observation (first diagnosis or follow-up); 5. diagnostic hypothesis made by the sender; 6. list of antigens and type of immunofluorescence analysis carried out; 7. absolute number of cells in the sample; 8. quality of the sample, in terms of viability; 9. general description of the gating procedure; 10. immunophenotype of blast cells; 11. description of cells surrounding blasts; 12. diagnostic conclusions; 13. definition of an antigen panel (when applicable) for the detection of minimal residual disease. As an example of a final report we present a case of acute myeloid leukaemia with t(8;21) translocation; in filling this report, we followed all the 13 points of the checklist described in the paper.